2023
DOI: 10.3390/app13021189
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Normal Stiffness and Shear Rate on the Shear Behaviors and Acoustic Emissions Characteristics of Artificial Rock Joints

Abstract: Understanding the asperity damage behaviors of joints during shearing is critical for evaluating the stability of deep underground engineering structures. In this paper, we prepared plaster joints and used them for direct shear tests under different normal stiffness (0–7 MPa/mm) and various shear rate (0.5–20 mm/min) conditions. The effects of normal stiffness and shear rate on mechanical behavior and AE characteristics were studied. With the increase of normal stiffness, the damaged area of the surface of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Furthermore, this study reveals a negative correlation between the peak shear strength of jointed specimens and the shear rate, and a positive correlation between it and the confining pressure. This conclusion is consistent with findings made by He et al 52 , Jiang et al 54 , Chen et al 56 , Zhu et al 57 . This can be explained by that the increased shear rate reduces the time for sufficient contact between joint planes, resulting in reduced frictional resistance.…”
Section: Discussion On the Test And Errorssupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, this study reveals a negative correlation between the peak shear strength of jointed specimens and the shear rate, and a positive correlation between it and the confining pressure. This conclusion is consistent with findings made by He et al 52 , Jiang et al 54 , Chen et al 56 , Zhu et al 57 . This can be explained by that the increased shear rate reduces the time for sufficient contact between joint planes, resulting in reduced frictional resistance.…”
Section: Discussion On the Test And Errorssupporting
confidence: 93%
“…He et al 52 conducted constant normal direct shear tests on jointed specimens at different shear rates, and investigated the shear performance with different joint roughness coefficients and joint wall compressive strengths, and under different normal stresses. Meng et al 53 and Jiang et al 54 conducted direct shear tests under various shear rate conditions to investigate the influence of normal stiffness and shear rate on the mechanical properties of the material. The results indicated that with an increase in shear rate, the peak shear stress of the joint decreased nonlinearly, while the peak shear displacement increased.…”
Section: Relative Workmentioning
confidence: 99%
“…Bolt-Grout interfaces were tested in shear using a CNC-type shear test set-up [37,38], which is shown in Figure 5. The apparatus consisted of a loading system, data acquisition and a controlling system.…”
Section: Test Apparatusmentioning
confidence: 99%
“…Further considering the unstable slip of structural planes, the slip-weakening friction law and the rateand-state friction law are proposed to describe the stick-slip instability (Dieterich, 1979;Rice, 1985). Extensive studies have been carried out to investigate the in uence of shear rate (v s ), σ n , normal stiffness (k n ), roughness, gouge layer and other factors on the shear mechanical properties for shear displacement-driven conditions, and have achieved remarkable research results (Li et al, 2022;Jiang et al, 2023). Furthermore, the shear mechanics under stress-driven conditions is gradually receiving more attentions.…”
Section: Introductionmentioning
confidence: 99%
“…µ is the ratio of τ s to σ n , which is used to represent the friction characteristics of structural planes. Studies have shown that unloading of σ n and loading of τ s contribute to the structural plane instability(Ji et al, 2019;Jiang et al, 2023). For numerical models 1 and 2, during the unloading of σ n , τ s remains constant, and the major principal stress is reduced, causing the initial stress state moves towards the failure envelope.…”
mentioning
confidence: 99%